The Turkish Government's Policy in Weakening the Gulen Movement - Audi Izzat Muttaqien; Gonda Yumitro (Britain International for Academic Research (BIAR) Publisher, 2022)
This article focuses on the policies of the Turkish Government in its efforts to weaken the Gulen Movement. The Gulen movement has grown in 150 countries has used its educational centers to spread ideas. Since the failed 2016 coup, sympathizers of the Gulen Movement have been branded Turkey and Islam as a threat. For the data collection method, the author used an in-depth literature review. This study used a qualitative approach to content analysis. The data collected is sourced from Mendeley and Harzing Publish or Perish, which then the data found will be further strengthened by various reviews. After the data was collected, the authors conducted an in-depth analysis and review in finding research data. There are two forms of policies carried out by the Turkish government, namely domestic policies, namely: (1) branding the Gulen Movement as a Terrorism Movement, (2) closing educational institutions and universities affiliated with the Gulen Movement, (3) threatening participants and followers of the Gulen Movement with imprisonment. Through false accusations, forced transfers, and kidnappings. Then for its foreign policy: (1) the Gulen Movement, which is branded internationally as the Terrorism Movement, (2) the closure of educational institutions and universities outside Turkey affiliated with the Gulen Movement, (3) threatening to arrest and hunt down the participants of the Gulen Movement and mention there is no safe place for them, including outside Turkey, (4) against the influence of Gulen's ideology with Sunni Islam in the process of spreading it. This research contributes to explaining the policy of the Turkish Government in depth through its efforts to weaken its Movement, the Gulen Movement, which is also an advantage over other similar studies. Then the drawback of this research is that it does not discuss further explanations of the Gulen Movement in detail.